Bioremoval of reactive dye Remazol Navy by kefir grains - Erdogdular, Ali Osman; Apar, Dilek Kilic (SPRINGER SINGAPORE PTE LTD, 2019)
Potential use of living and non-living kefir grains (small, gelatinous white/yellow irregularly shaped masses consist of live bacteria and yeasts) on removal of reactive dye Remazol Navy RGB from aqueous solutions were investigated. Experiments were carried out under different process conditions in order to optimize and model the bioremoval processes. At all conditions the living kefir grains exhibited higher dye removal efficiencies than the non-living grains. In 180 min, 96.3% and 79.4% dye removal was obtained with living and non-leaving kefir grains respectively, at pH 2, 25 degrees C for 100 mg/L initial dye concentration by using 2.4 g/L kefir grain. Maximum adsorption capacities by living and inactivated kefir grains were obtained at 400 mg/L initial dye concentration as 134.59 and 56.92 mg/g respectively. Consecutive batch studies show that the living kefir grains could be reused over at least 5 cycles with high dye removal efficiency without any nutrition supplement. The biosorption kinetics both for living and non-living kefir grains were best described with pseudo-first-order kinetic model. On the other hand the biosorption equilibrium for living and non-living kefir grains were better defined by Temkin and Langmuir isotherm models respectively. Results suggest that the kefir grains could be used efficiently, eco-friendly and economically for removal of dyes from aqueous solutions.
Keywords: Bioaccumulation; Biosorption; Kefir grain; Kinetic; Reactive dye; AQUEOUS-SOLUTION; PROCESS OPTIMIZATION; TEXTILE DYE; RED 198; REMOVAL; AZO; WASTE; DECOLORIZATION; ADSORPTION; Food Science & Technology